Effectiveness of video assisted teaching on knowledge and practice regarding suctioning of children on mechanical ventilator among nurses working in paediatric department - Sharma, Anurag; S., Subin (International Journal of Contemporary Pediatrics, 2023)
Background: Airway secretion clearance is a normal process that is essential for preventing respiratory infections, atelectasis, pulmonary haemorrhage and maintaining airway patency. In order to ensure this, effective and safe suction is necessary. Thus, endotracheal suctioning removes secretions which gets accumulated in the endotracheal tube through using negative suction pressure. The study aimed to assess the effectiveness of video assisted teaching on knowledge and practice regarding suctioning of children on mechanical ventilator among nurses working in pediatric department. Methods: Data were collected with the help of demographic-profile, Self-Structured knowledge questionnaire and Rating scale tool from 38 samples using Purposive sampling technique who met the inclusion criteria. The pretest data collected before intervention and post-test data collected after one week of video assisted teaching. Results: The result revealed that post intervention knowledge score was found to be more (20.44±2.68) than pre intervention knowledge score (14.31±2.77), t=9.19. Post intervention attitude score was found to be more (26.86±3.30) than pre intervention attitude score (18.52±3.68), t=8.17 at 0.05 level of significance. Conclusions: These findings revealed that the video assisted teaching programme on knowledge and practice was effective.